Efeito do farnesol sobre fatores de virulência de Candida albicans e Streptococcus mutans - Fernandes, Renan Aparecido [UNESP] (2015)
The aim of this study was to evaluate the activity of a quorum sensing molecule, farnesol, in biofilm formation of Candida albicans ATCC 10231 and Streptococcus mutans ATCC 25175. Initially farnesol was diluted in methanol and then in artificial saliva (AS). Minimum inhibitory concentration tests (MIC) of farnesol against Candida albicans ATCC 10231 cells and Streptococcus mutans ATCC 25175 suspension were based on the microdilution method. Farnesol was prepared at concentrations of 1.56, 3.125, 6.25, 12.5, 25, 50, 70, 150 and 300 mM, and placed in contact with biofilms in formation of Candida albicans and Streptococcus mutans for 48 hours. Its antibiofilm activity was determined by quantifying the total biomass (stained with crystal violet (CV)), enumeration of colony forming units (CFUs) and metabolic activity (XTT). It was further carried out a cell death time curve for both microorganisms studied. After the treatment with farnesol, the matrix of the biofilm was extracted and analyzed in terms of protein and carbohydrates, in addition to the pH test for S. mutans and examination of enzymatic activities of proteinase, fosfolipase and hemolytic for Candida albicans. The structure of biofilms was analyzed by scanning electron microscopy. The MIC values were 150 mM for C. albicans and 6.25 mM for S. mutans. Farnesol decreased the formation of single and mixed biofilms, with significant reductions of 37-90% and 64-96% respectively for the total biomass and metabolic activity. For single biofilms, farnesol concentrations equal to or higher than 3.125 mM promoted significant reductions (1,3-4,2log10; p <0.05) in the CFU for single biofilms, while in mixed biofilms the reductions (0,67-5,32log10; p <0.05) were noted at concentrations of 1.56 mM. For cell death curve after an hour in contact with those microorganisms, farnesol reduced 1 log10...